PERANCANGAN SISTEM ABSENSI BERBASIS MONITORING MENGGUNAKAN TEKNOLOGI FACE RECOGNITION - Kho, Gafery; Hotma Pangaribuan (LPPM Universitas Putera Batam, 2025)
Employee attendance is a crucial factor in determining company performance and productivity. Therefore, an accurate and efficient attendance system is needed to ensure compliance with working hours. This study aims to design a monitoring-based attendance system using Face Recognition technology at PT. Global Benua Bajatama. The technology is used to automatically detect and recognize employee faces. The research method applied is qualitative, involving system design using Unified Modeling Language (UML), database design, and testing the accuracy of facial detection as well as analyzing the system’s effectiveness. The results show that the face detection accuracy ranges from 80% to 95% under optimal conditions. These conditions include employees not wearing facial accessories such as masks, sunglasses, or safety helmets, and maintaining a face-to-camera distance of about 40–50 cm. Under these circumstances, the system can detect and recognize faces quickly and accurately, producing attendance data that meets the required specifications. The implementation of this system improves the efficiency of the attendance process and reduces the potential for errors compared to manual attendance recording.